LAYANAN PERPUSTAKAAN FAKULTAS KEDOKTERAN UMUM UNIVERSITAS BAITURRAHMAH MASA PANDEMI COVID-19 - Hasfera, Imca Pero (UIN Imam Bonjol Padang, 2021)
ABSTRACT Library services provided by librarians must meet the demands of information users in the pre- and post-covid-19 era. Various libraries are now facing a paradigm shift to meet the challenges brought by Covid-19. Instead of returning to normal library activities, librarians will return to the “new normal”. One of them is experienced by the Library of the Faculty of General Medicine (FK) Baiturrahmah University in Padang City. The presence of the Covid-19 pandemic is forcing librarians to have time to adapt pedagogical practices as well as learn new virtual technologies, and develop outreach plans to ensure continued library services in remote and online environments. Other changes to the FK UNBRAH library include a greater shift in acquisition from print to electronic resources. Services for remote systems may be a bigger point of emphasis. COVID-19 has no boundaries and is changing our lives and the way we work and minimizing face-to-face interactions. So that inevitably these changes have predicted the substantial way the FK UNBRAH library has shifted in terms of physical access to print collections, facilities, collections, services, spaces and operations as a result of the Covid-19 pandemic. The traditional approach used by libraries was abandoned, and new tactics were identified to be implemented in response to the current situation as the new normal with the help of Information and Communication Technology (ICT). Keywords: Library Services, Covid-19, University Libraries, Paradigm Change, Baiturrahmah University. ABSTRAK Layanan perpustakaan yang diberikan oleh pustakawan harus memenuhi tuntutan pengguna informasi di era pra dan pasca pandemi Covid-19. Berbagai perpustakaan kini menghadapi pergeseran paradigma untuk menghadapi tantangan yang dibawa oleh Covid-19. Alih-alih kembali ke aktivitas perpustakaan biasa, pustakawan akan kembali ke “normal baru”. Salah satunya yang dialami oleh Perpustakaan Fakultas Kedokteran Umum (FK) Universitas Baiturrahmah di Kota Padang. Kehadiran pandemi Covid-19 memaksa pustakawan memiliki waktu untuk menyesuaikan praktik pedagogis serta mempelajari teknologi virtual baru, dan mengembangkan rencana penjangkauan untuk memastikan layanan perpustakaan yang berkelanjutan di lingkungan jarak jauh dan online. Perubahan lain pada perpustakaan FK UNBRAH termasuk pergeseran yang lebih besar dalam akuisisi dari sumber daya cetak ke elektronik. Layanan untuk sistem jarak jauh mungkin menjadi titik penekanan yang lebih besar. COVID-19 tidak memiliki batas dan mengubah hidup kita dan cara kita bekerja dan meminimalkan interaksi tatap muka. Sehingga mau tidak mau perubahan tersebut telah memprediksi cara substansial perpustakaan FK UNBRAH telah bergeser dalam hal akses fisik ke koleksi cetak, fasilitas, koleksi, layanan, ruang dan operasi sebagai akibat dari pandemi Covid-19. Pendekatan tradisional yang digunakan oleh perpustakaan ditinggalkan, dan taktik baru diidentifikasi untuk dijalankan dalam menanggapi situasi saat ini sebagai normal baru dengan bantuan Teknologi Informasi dan Komunikasi (TIK). Kata Kunci: Layanan Perpustakaan, Covid-19, Perpustakaan Universitas, Perubahan Paradigma, Universitas Baiturrahmah.